Governance and leadership in agri-food systems and nutrition - Gillespie, Stuart; Nisbett, Nicholas (International Food Policy Research Institute, 2019)
This chapter first reviews the relationship between governance systems and processes (at various levels) and the nutrition sensitivity of agri-food systems, before reviewing the role of leadership in orienting such systems toward nutrition goals.